Wave separation analysis-derived indexes obtained from radial and carotid tonometry in healthy pregnancy and pregnancy-associated hypertension: Comparison with pulse wave analysis-derived indexes - Pereira, María M. (2022)
Background: Increased wave reflections assessed by pulse wave analysis (PWA) was proposed as one of the potential culprits of hypertension seen in women with pregnancy-associated hypertension (PAH). However, this statement has never been confirmed with “Wave Separation Analysis” (WSA), a more sophisticated mathematical approach that analyzes the amplitude and interaction between forward and backward aortic pressure waveform components. Objective: To characterize potential changes in pressure wave components of PAH compared to healthy non-pregnant (NP) women and women with normal pregnancies (HP) by using WSA and compared these findings with PWA-derived indexes; secondarily, to evaluate differences in WSA-derived indexes between subgroups of PAH (i.e., preeclampsia [PE] and gestational hypertension [GH]). Methods: Using radial and carotid applanation tonometry, we quantified in HP (n = 10), PAH (n = 16), and NP (n = 401): (i) PWA-derived indexes; (ii) WSA-derived indexes: forward (Pf) and backward (Pb) waveform components, backward component arrival time (PbAT), reflection magnitude (RM = Pb/Pf) and index [RIx = Pb/(Pf + Pb)]. Results: While PAH was associated with a higher Pf compared to HP and NP, Pb and PbAT were similar between the groups. Both GH and PE showed a higher Pf compared to HP, but only PE had a trend of presenting with higher Pb and lower PbAT compared to the other groups. Finally, PAH showed a trend of having lower RM and RIx compared to NP and HP, with no differences between GH and PE. Conclusion: PAH was associated with higher Pf, but not higher Pb, compared to NP and HP, although PE also demonstrated a trend of higher Pb.